The “Anti Hero” in Khairy Shalabi’s Novel Rihlat Al-Tarshaji wa Al-Hallwaji - Ababneh, Sami Mohammed (Dirasat: Human and Social Sciences, 2023)
Objectives: The paper tackles the concept of the “Anti Hero” and its presence in Khairy Shalabi’s novel Rihlat al-Tarshaji wa Al-Hallwaji. It discusses this concept, and its fictional formation, as well as the deep idea of its embodiment. Focusing on these elements is to illuminate the problems of reality while placing them in human consciousness. Methods: The paper illustrates its basic methodical concepts and extrapolates the vision and narrative structure of Shalabi’s novel. Accordingly, it begins with clarifying the concept of the “Anti Hero” and its manifestations in Arabic novels. Then, the paper analyzes the vision of Rihlat al-Tarshaji wa Al-Hallwaji’s hero and its narrative construction patterns. Results: The paper reveals that the hero of Khairy Shalabi’s Rihlat al-Tarshaji wa Al-Hallwaji is opposed to other novels built on the concept of “Anti Hero.” This calls for the necessity of meditating and rethinking about this concept. The novel causes the reader to end sympathy and solidarity with the character of the “hero” and to generate an opposite feeling about him, which is what Shalabi intends by using sarcasm. Also, the paper highlights that the novel consists of four structural patterns: Picaresque, historical, carnivalesque biography and travel narrative. Conclusion: The paper concludes that Khairy Shalabi’s Rihlat al-Tarshaji wa Al-Hallwaji is built on the concept of “Anti Hero.” This is reflected in the features and diversity of its structure, without being restricted to one narrative style.